2016
DOI: 10.1158/1078-0432.ccr-15-2872
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Cutaneous Adverse Drug Reactions during Anti-PD-1 Therapy

Abstract: Purpose: Immunotherapy has experienced impressive progress in cancer treatment. Antibodies against PD-1 improved survival in different types of cancer including melanoma. They are generally well tolerated. However, skin toxicities including pruritus, rashes, and vitiligo are reported. Although frequent, they have not been characterized further yet. In this analysis, we aimed to systematically assess and characterize the adverse cutaneous reactions observed in patients with melanoma treated with anti-PD-1 antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
157
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 28 publications
6
157
2
8
Order By: Relevance
“…Several authors reported higher numbers of skin irAEs in melanoma patients during nivolumab treatment. 4,5,7,8 An association between appearance of skin irAEs and OS in melanoma has been reported. [13][14][15]17 Similarly, our data suggest an association between skin irAEs and tumor response.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several authors reported higher numbers of skin irAEs in melanoma patients during nivolumab treatment. 4,5,7,8 An association between appearance of skin irAEs and OS in melanoma has been reported. [13][14][15]17 Similarly, our data suggest an association between skin irAEs and tumor response.…”
Section: Discussionmentioning
confidence: 97%
“…Rash and pruritus are frequent immune-related dermatologic adverse reactions (skin irAEs) during immunotherapy, which have been reported to occur in up to 25% of melanoma patients. 4,5,7,8 In NSCLC patients treated with nivolumab skin irAEs are reported in approximately 10% or more. 2,3,[9][10][11] Grading of toxicity is commonly classified according to Common Terminology Criteria for Adverse Events (CTCAE version 4.0).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic irAEs include enterocolitis, pneumonitis, hepatitis, nephritis, hypophysitis, and autoimmune thyroid disease. In addition, dermatologic toxicity is the most common irAE of checkpoint inhibitors and ranges from pruritus and mild dermatoses to severe reactions including Stevens-Johnson syndrome and toxic epidermal necrolysis 2 . Vitiligo-like depigmentation is well described in melanoma patients receiving immunotherapy with PD-1 inhibitors and may be associated with favorable outcomes 3 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is speculated that PD-1 antagonism results in the loss of T-cell homeostasis within the skin, thereby causing self-directed cytotoxic and inflammatory reactions [8]. This hypothesis was supported by Vivar et al [5] and Goldinger et al [9]. The former showed a significant increase in the expression of PD-L1 in lymphocytes and keratinocytes after the 3rd cycle of nivolumab (anti-PD-1 immune checkpoint antibodies) treatment as skin eruptions progressed from morbilliform eruptions to TEN.…”
mentioning
confidence: 95%
“…The former showed a significant increase in the expression of PD-L1 in lymphocytes and keratinocytes after the 3rd cycle of nivolumab (anti-PD-1 immune checkpoint antibodies) treatment as skin eruptions progressed from morbilliform eruptions to TEN. The latter demonstrated that immune checkpoint inhibitors can activate T cells and target keratinocytes leading to apoptosis which manifests clinically as TEN [9]. The mainstay of SJS/TEN treatment is supportive care, which includes identification and discontinuation of potential offending medications, appropriate wound care, maintenance of fluids and electrolytes homeostasis, temperature control, and consultation of appropriate specialties (ophthalmology and urology) for evaluation and support [10].…”
mentioning
confidence: 99%